Membangun Citra Merek Jemaat GPM Poka Ambon Melalui Optimalisasi Instagram Kreatif Sebagai Media Marketing - Kurniawan, Sabda Aji; Ningsih, Nadya Nurlailya; Hanoeboen, Bin Raudha A. (Universitas Methodist Indonesia, 2025)
The efficacy of Instagram as a marketing tool is attributable to its visual features, including Stories, Reels, and Insights. This community service program sought to optimize Instagram as a marketing platform for the Angkatan Muda Gereja Protestan Maluku (AMGPM) Cabang Sion Jemaat Tiberias I Poka. The program was developed in response to the organization's challenges in building its brand image, which was attributed to its members' limited digital knowledge. The program was meticulously structured in two phases: a preparatory phase that entailed interviews and observations to ascertain the community's needs, and an implementation phase comprising interactive workshops and open discussions. The program's success is evidenced by the enhancement of participants' skills in creative Instagram utilization, the strengthening of the community's brand image, and the fostering of innovation in social media management to better adapt to digital developments.